Global spatial analysis of Arabidopsis natural variants implicates 5′UTR splicing of LATE ELONGATED HYPOCOTYL in responses to temperature. (15th April 2018) - James, Allan B.; Sullivan, Stuart; Nimmo, Hugh G.
Abstract: How plants perceive and respond to temperature remains an important question in the plant sciences. Temperature perception and signal transduction may occur through temperature‐sensitive intramolecular folding of primary mRNA transcripts. Recent studies suggested a role for retention of the first intron in the 5′UTR of the clock component LATE ELONGATED HYPOCOTYL ( LHY ) in response to changes in temperature. Here, we identified a set of haplotypes in the LHY 5′UTR, examined their global spatial distribution, and obtained evidence that haplotype can affect temperature‐dependent splicing of LHY transcripts. Correlations of haplotype spatial distributions with global bioclimatic variables and altitude point to associations with annual mean temperature and temperature fluctuation. Relatively rare relict type accessions correlate with lower mean temperature and greater temperature fluctuation and the spatial distribution of other haplotypes may be informative of evolutionary processes driving colonization of ecosystems. We propose that haplotypes may possess distinct 5′UTR pre‐mRNA folding thermodynamics and/or specific biological stabilities based around the binding of trans ‐acting RNA splicing factors, a consequence of which is scalable splicing sensitivity of a central clock component that is likely tuned to specific temperature environments. Abstract : How plants perceive and respond to temperature remains an important question in the plant sciences. We investigated the global spatial distribution of haplotypes for the 5′UTR region of the core circadian clock component LATE ELONGATED HYPOCOTYL ( LHY ) and obtained evidence that haplotype influences temperature‐dependent splicing of LHY transcripts. Our work suggests that scalable splicing sensitivity tunes the circadian clock to specific temperature environments.